Perayaan Nyepi Umat Hindu Bali Bertindak Lokal dan Berpikir Universal - Yupardhi, W. Sayang (Institut Hindu Dharma Denpasar, 2018)
Hindu can’t be seprated from ritual including its holy day. In general, the Holy Day was celebrated by most of Hindu people in Bali since 426 AD and continues from one generation to the next. The objective of the Nyepi was to balance bhuana agung and bhuana alit that in human being implemented as power,vois and mind in a certain time needs to be recharged to bring back their power as what they were. In related to Nyepi, Melasti ritual is one of rituals held generaly 3 days before the Nyepi is celebrated where symbols of Gods and Godes of Dalem, Puseh, Desa Tamles are carry to the closet sea by foot or by car or bus to furefiying. Furthermore, a day before the Nyepi called pengerupukan where ofering (caru) was offered to evels to make them calm. During the celebration of the Nyepi, Bali fill very quite for 24 hours. It can be understood that during the 24 hours there was no air pulutions due to all of physical activities stop.for 24 hours. This is really a genius action. Where ever, all over the world, one look for it may not find the Nyepi like that, so it is very prestisious in universal live i.e. macro and micro balance. There is no cresh among sesame or other religions. At the end of the Nyepi, excactly aday after Nyepi called Ngembak Geni, the Hindu people are not hear yet their voice who act visiting each other as brother and sister to implement results of the Nyepi reflextion in order to start a new live . Actually that time is very good to make relationship between Hindu people and other people eith difference religion or other nations (take and give) as an implementation of a Hindu principle that we are all brother and sister.